Historical dictionary of the Chinese economy - Sullivan, Lawrence R.; Curcio, Paul (Historical dictionaries of Asia, Oceania, and the Middle East., 2018)
The Historical Dictionary of the Chinese Economy contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 400 cross-referenced entries on critical sectors of the economy including automobiles, banking and finance, national currency, economic regulation, trade and investment.